Energy Analysis of a Dual-Source Heat Pump Coupled with Phase Change Materials - Michele Bottarelli; Francisco Javier González Gallero (Energies, 2020)
Installation costs of ground heat exchangers (GHEs) make the technology based on ground-coupled heat pumps (GCHPs) less competitive than air source heat pumps for space heating and cooling in mild climates. A smart solution is the dual source heat pump (DSHP) which switches between the air and ground to reduce frosting issues and save the system against extreme temperatures affecting air-mode. This work analyses the coupling of DSHP with a flat-panel (FP) horizontal GHE (HGHE) and a mixture of sand and phase change materials (PCMs). From numerical simulations and considering the energy demand of a real building in Northern Italy, different combinations of heat pumps (HPs) and trench backfill material were compared. The results show that PCMs always improve the performance of the systems, allowing a further reduction of the size of the geothermal facility. Annual average heat flux at FP is four times higher when coupled with the DSHP system, due to the lower exploitation. Furthermore, the enhanced dual systems are able to perform well during extreme weather conditions for which a sole air source heat pump (ASHP) system would be unable either to work or perform efficiently. Thus, the DSHP and HGHE with PCMs are robust and resilient alternatives for air conditioning.